Plume —lid interactions during the Archean and implications for the generation of early continental crust - Piccolo, A; White, R; Kaus, B; Palin, R; Reuber, G (Elsevier, 2020)
Many Archean terranes are interpreted to have a tectonic and metamorphic evolution that indicates intra-crustal reorganization driven by lithospheric-scale gravitational instabilities. These processes are associated with the production of a significant amount of felsic and mafic crust, and are widely regarded to be a consequence of plume-lithosphere interactions. The juvenile Archean felsic crust is made predominantly of rocks of the tonalite–trondhjemite–granodiorite (TTG) suite, which are the result of partial melting of hydrous metabasalts. The geodynamic processes that have assisted the production of juvenile felsic crust, are still not well understood. Here, we perform 2D and 3D numerical simulations coupled with the state-of-the-art of petrological thermodynamical modelling to study the tectonic evolution of a primitive Archean oceanic plateau with particular regard on the condition of extraction of felsic melts. In our numerical simulations, the continuous emplacement of new, dry mafic intrusions and the extraction of the felsic melts, generate an unstable lower crust which drips into the mantle soon after the plume arrival. The subsequent tectonic evolution depends on the asthenosphere TP. If the TP is high enough (≥ 1500 ∘C) the entire oceanic crust is recycled within 2 Myrs. By contrast at low TP, the thin oceanic plateau slowly propagates generating plate-boundary like features.